THE URBAN MUSLIM THOUGHT IN THE AGE OF INFORMATION: MUHAMMADIYAH DIGITAL QUR’ANIC INTERPRETATION - Ni'mah, Siar; Hamzah, Amir; Hawirah, Hawirah; Umar, Umar; Amin, Saifuddin (AKADEMIKA: Jurnal Pemikiran Islam, 2022)
Advancements in information technology are profoundly impacting various aspects of human life, particularly within urban Muslim communities. Responding to the technological shifts, communities like Muhammadiyah engage in digital interpretation. Therefore, this study aimed to analyze Muhammadiyah interpretation, specifically focusing on Tafsir at-Tanwir through the Tarjih Channel Majelis Tarjih and Tajdid PP. Muhammadiyah. Two main aspects were also addressed, namely the methodology and the characteristics of digital interpretation by Muhammadiyah as presented in Tarjih YouTube Channel. A descriptive analytical Qualitative approach was adopted, and the collected data were then analyzed through data condensation, reduction, presentation, and conclusion. The results showed (1) the emergence of a new form of interaction with the Qur’an in the digital era, (2) the utilization of tahlily and maudhu’i methods in presenting Tafsir at-Tanwir, and (3) the active role of Tafsir at-Tanwir in shaping contemporary interpretations, specifically in the dissemination of interpretations digitally. In addition, the results showed that Muslims now have greater proximity and accessibility to Qur’anic interpretation compared to previous eras. This indicated that urban Muslims, specifically Muhammadiyah, contributed significantly to da'wah through digital media interpretation of Qur'anic verses on the Tarjih Channel.